2024
DOI: 10.1001/jamaoncol.2023.5033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biomarker Findings of Neoadjuvant Pembrolizumab and Carboplatin Plus Docetaxel in Triple-Negative Breast Cancer

Priyanka Sharma,
Shane R. Stecklein,
Rachel Yoder
et al.

Abstract: ImportanceAddition of pembrolizumab to anthracycline-based chemotherapy improves pathologic complete response (pCR) and event-free survival (EFS) in triple-negative breast cancer (TNBC). The efficacy of anthracycline-free chemoimmunotherapy in TNBC has not been assessed.ObjectiveTo assess the efficacy of the anthracycline-free neoadjuvant regimen of carboplatin and docetaxel plus pembrolizumab in TNBC.Design, Setting, and ParticipantsThis was an open-label phase 2 clinical trial including a single group of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…In the NeoPACT study, 83 patients with stage II to III disease and ER and PR less than 1% achieved a pCR rate of 58% using taxane and platinum-based agent combined with pembrolizumab for six cycles. 27 Our study used taxane and lobaplatin combined with anlotinib for 6 cycles, and obtained a pCR rate of 57.8%, which is similar to the NeoPACT study. According to the results of pCR rate, it could be interesting to further evaluate of neoadjuvant anlotinib plus taxane and platinum as an alternative regimen for patients with TNBC, who are not eligible for chemoimmunotherapy or anthracycline-based regimens in phase 2–3 randomized studies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the NeoPACT study, 83 patients with stage II to III disease and ER and PR less than 1% achieved a pCR rate of 58% using taxane and platinum-based agent combined with pembrolizumab for six cycles. 27 Our study used taxane and lobaplatin combined with anlotinib for 6 cycles, and obtained a pCR rate of 57.8%, which is similar to the NeoPACT study. According to the results of pCR rate, it could be interesting to further evaluate of neoadjuvant anlotinib plus taxane and platinum as an alternative regimen for patients with TNBC, who are not eligible for chemoimmunotherapy or anthracycline-based regimens in phase 2–3 randomized studies.…”
Section: Discussionsupporting
confidence: 74%
“… 9 These data also compare favorably with those from neoadjuvant chemoimmunotherapy regimens, in which toxic effects related treatment discontinuation rates of 23%, 23%, and 12% were reported by the KEYNOTE-522, Impassion031, and NeoPACT trials. 25 , 26 , 27 The hematological toxicities and gastrointestinal reactions are the most common AEs shared by neoadjuvant chemotherapy. The anthracycline drug increases the cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that TNBC tumors exhibit a tumor microenvironment (TME) enriched with immune cells, characterized by high levels of sTILs, PD-L1-positivity and up-regulated immune gene signatures [13,14,19,20]. These immune biomarkers exhibit correlations [13,20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, robust evidence suggests that a high level of stromal tumor-in ltrating lymphocytes (sTILs) in pre-treatment biopsied samples correlates with an increased rate of pCR in TNBC patients undergoing neoadjuvant chemotherapy [9][10][11][12][13][14]. However, there has been limited data regarding the impact of sTILs on response to different neoadjuvant chemotherapy regimens with or without pembrolizumab in TNBC patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is still controversy of whether need to combine anthracycline in TNBC therapy. phase II NeoPACT study ( 15 ) showed patients treated with preoperative anthracycline-free chemotherapy (carboplatin and docetaxel) with pembrolizumab achieved a pCR rate of 58% and a 3-year EFS of 86%. cTRIO study showed patients treated with 6 cycles of non-anthracycline (nab-paclitaxel + carboplatin + tislelizumab) achieved a pCR of 56.5% ( 11 ).…”
Section: Immunotherapy For Early-stage Tnbc (Etnbc)mentioning
confidence: 99%